Studi Perbandingan Hukum Pidana Islam Dan Hukum Positif Tentang Delik Perzinaan - muhammad Fikram; kamri Ahmad; Andi Tenri Sapada (Qawanin Jurnal Ilmu Hukum, 2021)
Abstract: Muh fikram. 04020170074: “Comparative Study of Islamic Criminal Law and Positive Laws Regarding Adultery Offenses”. Under the guidance of (Dr. KamriAhmad, SH., M. Hum., C.L.A) as the Chief Advisor and as the Advisory Member.This study aims to find out and analyze the classification of adultery in Islamic Criminal Law and the Criminal and to find out and analyze the similarities and differences between Islamic Criminal Law and Positive Law on Adultery Offenses.The research method used in writing this thesis is a normative juridical comparison between Islamic law and the Criminal Code (KUHP). Which uses a descriptive method with a qualitative approach,namely research that studies various legal norms. This research uses secondary data obtained from various literatures and regulations related to the problems inthe Thesis.The results of this study are that Article 284 only sex offenders who are bound by marriage can be categorized as adulterers and constitute a complaint offense which is included in the absolute complaint offense category, there must be a complaint first so that the offense can be processed. Meanwhile,in Islamic law, the criminal act of adultery becomes an ordinary offense, which means that anyone can complain about adultery, provided that the evidenceincludes four witnesses or confessions of the perpetrator.Recommendations of this research as an important note in the implementation of the applicable legal system. The understanding and settlement of the law and its enforcement must be clearly explained by the government to law enforcement officials in order to create a better legal order. Abstrak: Muh fikram. 04020170074:”Studi Perbandingan Hukum Pidana Islam Dan Hukum Positif Tentang Delik Perzinaan”. Di bawah bimbingan (Dr. Kamri Ahmad,SH.,M.Hum.,C.L.A) Sebagai Ketua Pembimbing Sebagai Anggota Pembimbing.Penelitian ini bertujuan Untuk mengetahui dan menganalisis penggolongan tindak pidana zina di dalam Hukum Pidana Islam dan KUHP Pasal 284 dan Untuk mengetahui dan menganalisis persamaan dan perbedaan antara Hukum Pidana Islam dan Hukum Positif tentang Delik Perzinaan.Metode penelitian Yang diigunakan dalam penulisan skripsi ini adalah Komparasi Yuridis normatif antara Hukum Islam Dengan Kitab Undang-UndangHukum Pidana (KUHP). Yang menggunakan metode deskriptif dengan pendekatan kualitatif yakni penelitian yang mempelajari berbagai norma-normahukum.penelitian ini menggunakan data sekunder yang diperoleh dari berbagai literature dan peraturan yang berkaitan dengan permasalahan di dalamSkripsi.Hasil Penelitian ini adalah bahwa Pasal 284 hanya pelaku persetubuhan yang sudah terikat perkawinan yang dapat dikategorikan sebagai Pezina dan merupakan delik aduan yang termasuk kategori delik aduan absoluth harus ada pengaduan terlebih dahulu supaya delik itu bisa diproses. Sedangkan dalam Hukum Islam tindak pidana perzinaan menjadi delik biasa yang artinya siapa saja dapat mengadukan perbuatan zina, dengan syarat terpenuhinya pembuktian meliputi empat orang saksi atau pengakuan pelaku.Rekomendasi penelitian inisebagai suatu catatan penting dalam pelaksanaan sistem hukum yang berlaku. Pemahaman dan penyelesaian hukum serta penegakannya harus dijelaskan secara tegas oleh pemerintah kepada aparatur penegak hukum demi terciptanyatatanan hukum yang lebih baik.